Growth of late preterm infants fed nutrient-enriched formula to 120 days corrected age-A randomized controlled trial - Karen P. Best; Karen P. Best; Lisa N. Yelland; Lisa N. Yelland; Carmel T. Collins; Carmel T. Collins; Andrew J. McPhee; Geraint B. Rogers; Geraint B. Rogers; Jocelyn Choo; Jocelyn Choo; Robert A. Gibson; et al. (Frontiers Media S.A., 2023)
ObjectivesWe aimed to compare the effects of nutrient-enriched formula with standard term formula on rate of body weight gain of late preterm infants appropriately grown for gestational age.Study designA multi-center, randomized, controlled trial. Late preterm infants (34-37 weeks' gestation), with weight appropriate for gestational age (AGA), were randomized to nutrient enriched formula (NEF) with increased calories (22 kcal/30 ml) from protein, added bovine milk fat globule membrane, vitamin D and butyrate or standard term formula 20 kcal/30 ml (STF). Breastfed term infants were enrolled as an observational reference group (BFR). Primary outcome was rate of body weight gain from enrollment to 120 days corrected age (d/CA). Planned sample size was 100 infants per group. Secondary outcomes included body composition, weight, head circumference and length gain, and medically confirmed adverse events to 365 d/CA.ResultsThe trial was terminated early due to recruitment challenges and sample size was substantially reduced. 40 infants were randomized to NEF (n = 22) and STF (n = 18). 39 infants were enrolled in the BFR group. At 120 d/CA there was no evidence of a difference in weight gain between randomized groups (mean difference 1.77 g/day, 95% CI, −1.63 to 5.18, P = 0.31). Secondary outcomes showed a significant reduction in risk of infectious illness in the NEF group at 120 d/CA [relative risk 0.37 (95% CI, 0.16-0.85), P = 0.02].ConclusionWe saw no difference in rate of body weight gain between AGA late preterm infants fed NEF compared to STF. Results should be interpreted with caution due to small sample size.Clinical Trial RegistrationThe Australia New Zealand Clinical Trials Registry (ACTRN 12618000092291). "mailto:maria.makrides@sahmri.com" maria.makrides@sahmri.com.